A productivity model for first thinning of Pinus patula using a tractor and double-drum winch in South Africa. Issue 2 (3rd April 2018) - Moloi, Thabo; Brink, Michal; Chirwa, Paxie W; Ngulube, Elisha
Abstract : The productivity of skidding tractors in intermediate harvesting operations has not been determined in Mpumalanga, South Africa. The objective of this study was to develop a productivity model using a farm tractor in first thinning operations in Pinus patula compartments. A work study design was used to assess the performance of a skidding agricultural tractor. From 350 samples, important data variables collected were elemental times for each work cycle, extraction distance, slope and load volume. Stepwise and subsets regression analyses were conducted prior to multiple linear regression analysis. Analysis of variance was used to compare mean productivity estimates of the different models developed. Results showed that the best model was estimated by an interaction of distance × slope ( ds ), distance × load volume ( dv ) and slope × load volume ( sv ) as follows: ln( ŷ 2 ) = 1.33–0.00154 ds + 0.00174 dv + 0.161 sv . The mean estimate for this model was 5.036 m 3 m h −1 . The developed models predicted similar results to estimation results of the observed model, although there were statistically significant ( P < 0.001) differences among mean estimates (3.6–5.5 m 3 m h −1 ). All of the three models yielded R 2 adj. = 38%; SE = 0.458% at P < 0.001. It can be speculated that the remaining variation not explained by the models may be associated with long extraction distances, delays and the effect of slope as a main variable in the model. While the developed models mirrored reasonably well with the observed estimates of skidding productivity, these models should not be stretched to conditions dissimilar to those of their generation. Future research focus should be made on (1) effects of weather conditions and vehicular characteristics on skidding productivity and (2) the effect of winching lines on skidding productivity.